The Role of Noncoding RNAs in B-Cell Lymphoma - Li, Jingwen; Zou, Jing; Wan, Xiaoyue; Sun, Chunyan; Peng, Fei; Chu, Zhangbo; Hu, Yu (Frontiers in Oncology, 2020)
In recent years, emerging evidence has suggested that non-coding RNAs (ncRNAs) participate in nearly every aspects of biological processes, and play a crucial role in the genesis and progression of numerous tumors, including B-cell lymphoma. The exploration of ncRNA dysregulations and their functions in B-cell lymphoma provides new insights into lymphoma pathogenesis, and is important for indicating future clinical trials and optimizing the diagnostic and therapeutic strategies. In this review, we summarized the role of ncRNAs in B-cell lymphoma, and discussed their potential in clinical applications.